Culture of the careless and vulnerability to disasters: marks of the radioactive accident with cesium-137 in Goiânia (Brazil) (Research, Society and Development, 2020)
This study aims to analyze the practices and representations related to coping with the radioactive disaster that occurred in the city of Goiânia (Brazil), through the analysis of the documentary film “Cesium 137 - the glow of death”. The research was structured under the perspective of the domain of visual culture and studies on disaster sociology and disaster risk management, being developed through film analysis and with the support of thematic-categorical content analysis. The film was treated in depth in relation to the sociological and content aspects, highlighting symbolic elements that portrayed the practices and representations of radio-injured citizens. The research results were structured according to the operations of description, decomposition and criticism and analysis of film content. The reports contained in the film were coded, segmented into recording units and organized into two empirical categories: culture of the careless and vulnerability to radioactive disasters. It was concluded that the film structure leads to the reading of the representation of the sectorial and technical unpreparedness to deal with disaster situations. This aspect highlights the need for management and governance practices that effectively link sustainability and security with the phenomena of caring for life, in cases of radioactive risks. In addition, the study highlights the potential of documentary films to analyze the phenomena of public health emergencies and disasters, especially of groups most vulnerable to such situations.